(untitled) (Eternitas: Jurnal Teknik Sipil, 2024)
In an effort to stimulate the economy in Sorong Regency, transportation infrastructure is needed that can support the economy in the area, so that alternative roads are built to facilitate the community’s economy to carry out activities, both accessibility and mobility of goods and services. One way to ensure that the thickness of the pavement does not suffer damage and can be used for a relatively long period of time is that the pavement structure needs to be planned properly. The aim of this research is to determine the thickness of the flexible pavement layer required on the Aimas Ring Road road section so that it meets needs. In planning pavement thickness, there are several methods that can be used. The method used to plan the thickness of road surface layers is the Component Analysis Method. The research results show that the thickness of the surface layer uses MS 774 kg lasbutag with a thickness of 8 cm and the top foundation layer uses class A aggregate material with a minimum thickness = 20 cm. Meanwhile, for the lower foundation layer, class B sirtu/pitrun with a minimum thickness of 10 cm is used